Biotechnologies and Biomimetics for Civil Engineering - Pacheco Torgal, Fernando; Labrincha, J. A.; Diamanti, M. V.; Yu, C.-P; Lee, H. K. (Springer International Publishing : Imprint: Springer, 2015)
Putting forward an innovative approach to solving current technological problems faced by human society, this book encompasses a holistic way of perceiving the potential of natural systems. Nature has developed several materials and processes which both maintain an optimal performance and are also totally biodegradable, properties which can be used in civil engineering. Delivering the latest research findings to building industry professionals and other practitioners, as well as containing information useful to the public, 'Biotechnologies and Biomimetics for Civil Engineering' serves as an important tool to tackle the challenges of a more sustainable construction industry and the future of buildings.